Field Trials of Health Interventions A Toolbox - Smith, Peter G.; Morrow, Richard H.; Ross, David A.; Open Textbook Library (Open Textbook Library, 2015)
Before new interventions can be used in disease control programmes, it is essential that they are carefully evaluated in "field trials", which may be complex and expensive undertakings. Descriptions of the detailed procedures and methods used in trials that have been conducted in the past have generally not been published. As a consequence, those planning such trials have few guidelines available and little access to previously accumulated knowledge. In this book the practical issues of trial design and conduct are discussed fully and in sufficient detail for the text to be used as a "toolbox" by field investigators. The toolbox has now been extensively tested through use of the first two editions and this third edition is a comprehensive revision, incorporating the many developments that have taken place with respect to trials since 1996 and involving more than 30 contributors. Most of the chapters have been extensively revised and 7 new chapters have been added.
Chapter 1 Introduction to field trials of health interventions -- Chapter 2 Types of intervention and their development -- Chapter 3 Reviewing the literature -- Chapter 4 Trial design -- Chapter 5 Trial size -- Chapter 6 Ethical considerations -- Chapter 7 Trial governance -- Chapter 8 Preparing grant applications -- Chapter 9 Community engagement -- Chapter 10 Censuses and mapping -- Chapter 11 Randomization, blinding, and coding -- Chapter 12 Outcome measures and case definition -- Chapter 13 Preliminary studies and pilot testing -- Chapter 14 Questionnaires -- Chapter 15 Social and behavioural research -- Chapter 16 Field organization and ensuring data of high quality -- Chapter 17 Field laboratory methods -- Chapter 18 Budgeting and accounting -- Chapter 19 Intervention costing and economic analysis -- Chapter 20 Data management -- Chapter 21 Methods of analysis -- Chapter 22 Phase IV studies -- Chapter 23 Reporting and using trial results
In English.
Description based on online resource
Keywords: Medicine -- Textbooks